Opinions on the Need for Digital and Pedagogical Competences in Vocational Training - Lessons from an Empirical Study - Bacsa-Ban, Anetta; Kolacsek, Sandor (IEEE International Conference and Workshop in Óbuda on Electrical and Power Engineering (Online), 2024)
For vocational teachers today, it is crucial to have pedagogical and digital competences in addition to professional competences. Pedagogical skills are essential to enable trainers to effectively transfer knowledge and motivate learners. An empathic and supportive teaching approach helps to promote active participation and engagement of learners and creates a positive learning environment. Moreover, digital competences are essential in modern education, which is rapidly becoming digital. Teachers need to keep up with the evolution of digital tools and platforms to provide interactive and flexible education that is adapted to the needs of learners and the expectations of the labour market. The research described in this study, conducted among VET teachers, can make a significant contribution to the development of these competences. It can reveal the current competences of teachers and identify needs for improvement. For example, it could reveal how well they feel prepared to use digital tools and what further training they need. On the basis of this information, educational institutions can develop targeted training programmes and support schemes to help develop pedagogical and digital competences.